Strengthening Social Capital Through Digital Platform: Neighborhood Community In DKI Jakarta - Eka Putri, Syora Alya; Safira, Fidan; Nadhira, Rizka; Hamdi, Hamdi; Debineva, Ferena; Putra, Nafiza Samditya; Nandika, Reisa Siva; Qurani Putri, Dinda Mutiara; Nagari, Ukhti Paundria; Ervi, Tivani Shakilla (UI Scholars Hub, 2023)
This study investigates how digital platforms can be leveraged to strengthen social capital and thus support sustainable urban development in Jakarta. Despite positive strides, there are several obstacles that hinders the optimal utilization of digital platforms in terms of information dissemination and enhancing stakeholder trust: (1) constraints posed by the communication medium; (2) digital literacy of stakeholders, and (3) ineffective participation of community members. Employing a qualitative method, this case study reveals that stakeholders across all levels play a pivotal role in encouraging participation among community members. Moreover, the findings indicate that utilizing integrated digital platforms for information management within neighborhood communities may foster collaboration, creating a space for inclusive discussions between regional administrators and the community. Strengthened networks resulting from the process may in turn contribute to regional development, since the collective capacity to address challenges is improved as well.